Control of cacao (Theobroma cacao)diseases in Santo Domingo de los Tsachilas, Ecuador = Control de enfermedades del cacao (Theobroma cacao)en Santo Domingo de los Tsáchilas, Ecuador - Anzules Toala, Vicente Danilo; Pazmiño Bonilla, Elvis Danilo; Alvarado Huamán, Leonel Eduardo; Borjas Ventura, Ricardo Roberto; Castro Cepero, Viviana (2022)
Introduction. Ecuador occupies the fourth place in cocoa exports with 293,487 tons per year, produced on 559,617 hectares. However, its yield per hectare is low mainly due to the presence of pathogens that affect the pods. Objective. To evaluates different methods of control of pathogens of the Theobroma cacao cv 'CCN-51' pod.Materials and methods. The work was carried out in Luz de America, Santo Domingo de los Tsachilas, Ecuador, between 2016 and 2017. The treatments were the result of the combination of cultural practices + two fungicides (Chlorothalonil and Pyraclostrobin) + one biofungicide Serenade® (Bacillus subtilis QST713), with and without fertilizers. In total, 16 treatments were evaluated with 3 replicates or blocks, installed in a commercial cocoa plantation cv 'CCN-51' and under a Randomized Complete Block Design (RCBD). Results. The use of fungicides (chemical and biological), decreased the incidence of moniliasis (Moniliophthora roreri), black pod rot (Phytophthora spp.), and cherelle wilt; but the application of fertilizers did not increase the effectiveness of these products. Treatment with only cultural practices did not decrease the final incidence of moniliasis, nor of brown rot, in contrast, the final incidence of cherelle wilt increased. The number of pods and the yield were not directly related and the highest yield of fermented and dry cocoa, corresponded to T9 [Cultural labors + Serenade® (0.2 kg ha-1) (every 15 days) + Fertilizer (0.3 kg ha-1) + Fertilizer (1 kg plant-1)], a treatment that also had the highest net income per hectare. Conclusion. Chemical and biological control can manage cocoa pods pathogens. The integration of both control methods allowed the cocoa producer to obtain greater income.
Introducción. Ecuador ocupa el cuarto lugar en exportaciones de cacao con 293 487 toneladas al año, producidas en 559,617 hectáreas. Sin embargo, su rendimiento por hectárea es bajo debido principalmente a la presencia de patógenos que afectan la mazorca. Objetivo. Evaluar métodos de control de patógenos de la mazorca de Theobroma cacao cv 'CCN-51'. Materiales y métodos. El estudio se llevó a cabo en Luz de América, Santo Domingo de los Tsáchilas, Ecuador, entre 2016 y 2017. Los tratamientos fueron el resultado de la combinación de labores culturales + dos fungicidas (Clorotalonil y Pyraclostrobin) + un biofungicida Serenade® (Bacillus subtilis QST713), con y sin fertilizantes. En total se evaluaron dieciséis tratamientos con tres réplicas o bloques, instalados en una plantación comercial de cacao cv 'CCN-51' y bajo un diseño de bloques completos al azar (DBCA). Resultados. El uso de fungicidas (químicos y biológicos), disminuyó la incidencia de la moniliasis (Moniliophthora roreri), pudrición negra de la mazorca (Phytophthora spp.) y cherelle wilt; pero la aplicación de fertilizantes no aumentó la efectividad de estos productos. El tratamiento solo con labores culturales, no disminuyó la incidencia final de la moniliasis, tampoco de la pudrición negra de la mazorca, en cambio, aumentó la incidencia final del cherelle wilt. El número de mazorcas y el rendimiento no estuvieron directamente relacionados y el mayor rendimiento de cacao fermentado y seco, correspondió al T9 [labores culturales + Serenade® (0,2 kg ha-1) (c/ 15 días) + fertilizante, (0,3 kg ha-1) + abono (1 kg planta-1)], tratamiento que también tuvo el mayor ingreso neto por hectárea. Conclusión. El control químico y biológico pueden combatir patógenos de la mazorca de cacao. La integración de los dos métodos de control permitió al productor obtener mayores ingresos.
En Revista Agronomía mesoamericana
Volumen 33, número 1 (enero - abril 2022)
Descripción basada en el contenido visto el 26 de Octubre, 2023
También disponible en formatos EPUB, HTML, XML y MP3 (español e ingles)
Keywords: CACAO -- ENFERMEDADES Y PLAGAS -- ECUADOR; MICROORGANISMOS FITOPATOGENOS -- CONTROL -- ECUADOR; FUNGICIDAS; CACAO -- CONTROL DE PLAGAS